PENGEMBANGAN SISTEM INFORMASI KETENAGAKERJAAN PADA BPBD OKU MENGGUNAKAN EMBARCADERO XE2 - Santoso, Dwi; Wisnumurti, Wisnumurti; Kadarsih, Kadarsih (Universitas Mahakarya Asia, 2024)
Population is a science related to techniques of collecting, investigating, recording and processing population data which consists of processing birth data, processing death data, processing data on population movements and arrivals. Population data processing is the main activity carried out by the Village, where in carrying out population data processing it must be done quickly, precisely and accurately. However, in reality there are still many government agencies that are still processing population data manually, therefore a population data processing information system is needed that can assist in processing population data, and is able to bridge the process of reporting population data from villages to sub-districts so as to speed up the service process. towards the community and influencing the optimization of employee work processes in village and sub-district offices. This information system was built using the waterfall methodology which consists of stages of analysis, design using Data Flow Diagrams to design functional models and Entity Relationship Diagrams to describe the data model, coding using the Embarcadero programming language, is the final stage of the methodology used. With the construction of this system, it can facilitate the process of processing population data at the village level and simplify the process of reporting to the sub-district level. Keywords: Information System, Population Data Collection, Embarcadero XE2